Sistem Kendali Proporsional pada Robot Penghindar Halangan (Avoider) Pioneer P3-DX - Jayadi, Akhmad; Susanto, Try; Adhinata, Faisal Dharma (Majalah Ilmiah Teknologi Elektro; Vol 20 No 1 (2021): (Januari - Juni ) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2021.v20i01.P05, 2021)
The basic ability that a mobile robot must have is to avoid obstacles, by being able to avoid obstacles, the robot will be able to do its job well without having to hit any obstacles, because by hitting an obstacle it will make the robot take longer to complete the mission even the robot can experience disorientation With the implementation of a control system on obstacle avoidance robots, the robot can overcome existing obstacles. Proportional control is a simple and easy to use control on a mobile robot, with eight sensors on the robot making the robot more sensitive to obstacles in front of it, so the pioneer type mobile robot P3-DX was used in this study. The robot has been able to pass through the existing obstacles with a Kp value of 2 and a constant speed of 4 without hitting it.